Software engineering for science - Carver, Jeffrey; Hong, Neil P. Chue; Thiruvathukal, George K. (CRC Press, 2017)
"Software Engineering for Science provides an in-depth collection of peer-reviewed chapters that describe experiences with applying software engineering practices to the development of scientific software. It provides a better understanding of how software engineering is and should be practiced, and which software engineering practices are effective for scientific software. The book starts with a detailed overview of the Scientific Software Lifecycle, and a general overview of the scientific software development process. It highlights key issues commonly arising during scientific software development, as well as solutions to these problems. The second part of the book provides examples of the use of testing in scientific software development, including key issues and challenges. The chapters then describe solutions and case studies aimed at applying testing to scientific software development efforts. The final part of the book provides examples of applying software engineering techniques to scientific software, including not only computational modeling, but also software for data management and analysis. The authors describe their experiences and lessons learned from developing complex scientific software in different domains"- Resumé vydavatel
Keywords: softwarové inženýrství; věda; zpracování dat; software engineering; science; data processing; kolektivní monografie; elektronické knihy; collective monographs; electronic books